2014
DOI: 10.1039/c4cc07275h
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-mediated ‘turn-off/turn-on’ nanozyme activity of gold nanoparticles for kanamycin detection

Abstract: A new ultrafast and highly sensitive 'turn-off/turn-on' biosensing approach that combines the intrinsic peroxidase-like activity of gold nanoparticles (GNPs) with the high affinity and specificity of a ssDNA aptamer is presented for the efficient detection of a model small molecule kanamycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
116
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(120 citation statements)
references
References 34 publications
0
116
1
Order By: Relevance
“…21 We recently demonstrated that natural amino acids such as tyrosine can be employed as unique reducing agents for the synthesis of charge-switchable metal nanoparticles. 24,25 In our recent work, the control of nanoparticle surface corona through this strategy allowed us to efficiently bind bulky clusters of polyoxometalates on the surface of tyrosine-reduced Au and Ag nanoparticles, which provided bacterial targeting attributes to these nanomaterials without causing toxicity to mammalian cells. This unique property of amino acids provides a facile handle to control the nanosurface chemistry to facilitate the binding of a variety of molecules through electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…21 We recently demonstrated that natural amino acids such as tyrosine can be employed as unique reducing agents for the synthesis of charge-switchable metal nanoparticles. 24,25 In our recent work, the control of nanoparticle surface corona through this strategy allowed us to efficiently bind bulky clusters of polyoxometalates on the surface of tyrosine-reduced Au and Ag nanoparticles, which provided bacterial targeting attributes to these nanomaterials without causing toxicity to mammalian cells. This unique property of amino acids provides a facile handle to control the nanosurface chemistry to facilitate the binding of a variety of molecules through electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the above tagging strategies, nanozyme tags are also often used in other immunoassays or immuno‐like assays (Das, Dhiman, Kapil, Bansal, & Sharma, ; Sharma et al., ). For example, Wu, Duan, Qiu, Li, and Wang () reported a colorimetric aptasensor platform for detecting Salmonella enterica serovar typhimurium ( S. typhimurium ) using the POD‐like ZnFe 2 O 4 ‐reduced graphene oxide nanostructures (ZnFe 2 O 4 /rGO) as a signal tag.…”
Section: Principles Of Detection Using Enzyme‐mimetic Nanomaterialsmentioning
confidence: 99%
“…Otherwise, nanozymes might change their original biocompatibility and these shielding compounds could be another toxic source. Once the surface protection is reversible, it is difficult to achieve in living systems due to easy formation of protein coronas around nanomaterials . Therefore, nanozymes urgently await the development of a fundamental approach for inhibiting their intrinsic peroxidase‐like activity in order to diminish their cytotoxicity while also retaining surface accessibility for other enzyme‐like activities.…”
Section: Introductionmentioning
confidence: 99%